Small radial flow sorghum (Sorghum bicolor (L.). Moench) thresher - Sobrinho, Antônio Timóteo; Martyn, Peter John; Mantovani, Evandro Chartuni; Fontes, Luis Antônio Nogueira (Pesquisa Agropecuaria Brasileira, 1995)
A small sized radial flow grain sorghum thresher was developed at the Department of Agricultural Engineering of the Universidade Federal de Viçosa with the cooperation of the National Maize and Sorghum Research Center of Embrapa. The machine was built of steel bars, pipes, rods, and sheet, using simple techniques (cutting, welding and lathe machining). Two roller bearings were the only special parts used. The power unit was either a 1.5 HP electric motor or a 3.5 HP gasoline engine. A threshing capacity ranging from 85 to 128 kilograms per hour was measured when evaluated with 15% to 24% w.b. grain sorghum.